Building a Winning Team: PT XYZ’s Approach to Optimizing Performance through Discipline and Culture - Mutmainah, Mutmainah (Dinasti International Journal of Digital Business Management, 2024)
The purpose of this study is to find out and analyze: (1) Discipline (2) Organizational Culture (3) Employee Performance (4) Effect of Discipline and Organizational Culture on Employee Performance. The research method used was an explanatory survey, descriptive survey and Path Analysis. Based on the results of the study found that there are other factors that make targets in the company have not been achieved and a large number of employees delay, is another variable from Discipline and Organization Culture. PT. XYZ must find other variables and improve so that employee performance increases.